Ovarian toxicity of environmental contaminants: 50 shades of grey - Dominguez, M. A.; Sadeu, J. C.; Guerra, M. T. [UNESP]; Furlong, H. C.; Baines, Sharnjit; Foster, Warren G. (Springer Nature, 2016)
Exposure to environmental contaminants is thought to be important in the development of adverse effects on reproductive health. While the adverse effects of environmental contaminants on semen quality and testicular function have been well studied, effects on ovarian function are less well defined. Epidemiological studies have linked exposure to environmental contaminants with adverse effects on menstrual cycle characteristics, infertility, and earlier age of menopause onset; yet direct evidence of effects on ovarian function is lacking. Environmental contaminant concentrations have been quantified in human ovarian follicular fluid establishing target tissue exposure; however, such data is sporadic and limited to women undergoing assisted reproductive therapies making generalization of results to the broader population of women difficult. We note that the relationship between serum and follicular fluid concentrations can be orders of magnitude different and thus target tissue distribution requires further study. Animal studies revealed effects of environmental contaminants on ovarian follicle dynamics, oocyte maturation, steroidogenesis, and epigenetic changes. Issues of dosing such as concentration of test chemicals used, route of administration, and use of multiple dose groups remain important limitations of the current literature. While animal studies establish a basis for biological plausibility of effects and support conclusions of reproductive hazard, we conclude that exposures in the general human population are too low to present a demonstrable risk to human ovarian function.
Keywords: Chemical contaminants; Ovary; Steroidogenesis; Toxicants; Toxicology